The Impact of Human Resource Management Practices on Organizational Performance: The Case of Libyan International Medical University - Mailud Balal; Abdilrahman Ebrahim; Abdalmanam Abrahim; Jassem Emghieb (Journal of Management Research, 2024)
This study aimed to investigate the impact of human resource management practices on organizational performance at Libyan International Medical University. The population consisted of 400 employees. The stratified randomized sample consisted of 196 employees. To reach the purpose of this study, data were collected from 151 employees using the questionnaire adopted from Al Shaikhly (2017). The questionnaire was revised, and validated by the supervisors. Statistical techniques such as descriptive statistics, Cronbach’s alpha, multiple regressions, and stepwise regression were used to test the hypotheses. The results showed that there is a significant impact of human resource management practices (planning & recruitment, training program, and performance appraisal) on the organizational performance of Libyan International Medical University at level (α <0.05). The results also showed that the performance appraisal variable has the most impact on organizational performance. On the other hand, the results also showed that compensation management had no impact on the organizational performance of Libyan International Medical University. The study limitations were the lack of previous studies published in Libya related to this topic, also the data were not normally distributed, and just 46% of variations in the organizational performance are explained by human resource management practices in this study. The study recommended conducting more research on the topics addressed in this study to acquire a deeper and broader understanding of human resource management practices.